(untitled) (Advancements in Homeopathic Research, 2022)
Allergic rhinitis is one of the most commonly occurring diseases that severely affects the quality of life of the patient. It is an IgE mediated hypersensitivity disease of mucous membranes of nasal airways characterised by sneezing, nasal congestion and discharge.The importance of this study is to find the effectiveness of homoeopathic medicines in treatment of allergic rhinitis. Moderate results were seen after giving homoeopathic treatment as the t-calculated value with level of significance P at a differential field 29 is greater i.e. 9.918, for number of episodes of allergic rhinitis per week after giving homoeopathic medicines than the t- table value with level of significance P = 0.01, i.e. 2.756.